Reporting Disasters : Famine, Aid, Politics and the Media. - Franks, Suzanne (Oxford : C. Hurst and Company (Publishers) Limited, 2014)
Ethiopia 1984: A groundbreaking account of the reporting of a famine and its unintended long-term consequences.
Cover -- Contents -- List of Illustrations -- Preface and Acknowledgements -- Introduction: Arguing About Famine -- 1. How Famine Captured the Headlines -- 2. Global Story: National Response -- 3. A Revolution in Giving -- 4. Misunderstanding the Famine: Telling the Story Wrong -- 5. The Humanitarian Dilemma -- 6. Too Tight an Embrace? The Agencies and the Media -- 7. Interpreting Africa -- 8. Real Media Effects -- Notes -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- Y -- Z.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Disasters--Press coverage--Moral and ethical aspects; Electronic books